Determinants of Voluntary Greenhouse Gas Emission Disclosure: An Empirical Investigation on Turkish Firms - Akbas, Halil Emre; Canikli, Seda (MDPI, 2019)
Firms worldwide have been facing an increasing pressure to disclose their Greenhouse Gas (GHG) emissions since GHG emissions are seen as the main source of global warming which is one of the most challenging problems that the world is faced with. For this reason, voluntary GHG disclosure represents a growing area of research interest. However, the existing research generally focuses on developed countries. In this sense, the present paper aims to contribute to the existing GHG disclosure literature by analyzing the determinants of voluntary disclosure of firms operating in a developing country, Turkey. The effects of both financial characteristics and board structures of firms on voluntary disclosure decisions are analyzed as the possible determinants of GHG disclosures of Turkish firms. We use two proxies for assessing the firms' GHG disclosures. The first proxy, sensitiveness tendency, indicates the response behavior of firms to the Carbon Disclosure Project (CDP) survey. The second proxy, namely, transparence tendency, represents the disclosure behavior of firms. Using logistic regression models with a sample of 84 listed Turkish companies which were included in the Carbon Disclosure Project survey in 2014, 2015 and 2016, we find that firm size, institutional ownership and market value are positively related to the sensitivity of sampled firms, while board size is negatively related. On the other hand, our results indicate that firm size, profitability and institutional ownership have positive impacts on the transparency of Turkish listed firms.
Keywords: greenhouse gas disclosure; global warming; Turkish firms; firm characteristics; corporate governance; Carbon Disclosure Project; SOCIAL-RESPONSIBILITY DISCLOSURE; MARKET-TO-BOOK; CLIMATE-CHANGE; ENVIRONMENTAL DISCLOSURE; CORPORATE DISCLOSURE; CARBON EMISSIONS; GOVERNANCE; BUSINESS; PERFORMANCE; SIZE; Science & Technology - Other Topics; Environmental Sciences & Ecology